A study of some variables related to Headmasters Trends of Secondary Stages of EL-OUED about the subject of Physical Education and Sports - Merzougui, Samir; Beggar, Nacer; Houiche, Ali (Al-Jamie Journal In Psychological Studies and Educational Sciences, 2022)
The study aims to identify the trends of Headmasters in secondary stages about the subject of physical education and sports. This is in relation to some variables, including, gender of Headmasters, qualifications (university, non-university). We conducted an exploratory preliminary study. The descriptive approach is appropriate to conduct such studies, which focus on studying the trends, opinions and tendencies. the study population consisted of all Headmasters of the secondary stages in the province of El-Oued, and depending on the comprehensive survey sample. The total of 50 Headmasters of secondary schools including 10 female and 40 males. Finally, the study concluded the following results: The study confirmed that secondary Headmasters of EL-OUED score positively towards the subject of physical education and sports on all three dimensions of the scale and the scale as a whole. There are significant differences between the two groups of Headmasters divided according to academic qualifications in the three dimensions and the scale as a whole. There are no statistically significant differences between Headmasters according to gender (male/female) on all three dimensions of the scale and the scale as a whole.